Maya Postclassic persistence in the Birds of Paradise Wetland Fields, Belize - Lara M. Sánchez-Morales; Timothy P. Beach; Sheryl Luzzadder-Beach; Samantha Krause; Duncan Cook; Byron Smith; David Lentz; Carlos Quiroz; William Pratt; Lori Phillips; Thomas Guderjan; Colleen Hanratty; et al. (Proceedings of the National Academy of Sciences, 2026)
Rapid decay of organic artifacts obscures our view of ancient tropical settlements. We present a study of architecture and artifact assemblages from an ancient settlement excavated at the Birds of Paradise (BOP) fields, the largest lidar and field-validated ancient Maya wetland field complex. The site’s unique setting preserved architectural wood and provides exceptional evidence of Maya Terminal Classic (CE 800 to 1000) to Postclassic (CE 1000 to 1500) persistence within tropical wetlands through periods of large-scale societal and climate change. A new Bayesian chronological model tightens the occupation history for the broader BOP wetlands based on 14 new radiocarbon dates of wood and charcoal from this settlement. These wetlands and their preserved ancient wood face imminent destruction through modern land uses.